2020
DOI: 10.1002/ece3.6400
|View full text |Cite
|
Sign up to set email alerts
|

Drought mildly reduces plant dominance in a temperate prairie ecosystem across years

Abstract: Shifts in dominance and species reordering can occur in response to global change. However, it is not clear how altered precipitation and disturbance regimes interact to affect species composition and dominance. We explored community‐level diversity and compositional similarity responses, both across and within years, to a manipulated precipitation gradient and annual clipping in a mixed‐grass prairie in Oklahoma, USA. We imposed seven precipitation treatments (five water exclusion levels [−20%, −40%, −60%, −8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…We found that responses were species-specific as hypothesized. Our previous study 43 on species-specific responses to precipitation and clipping showed a small number of significant interactive effects between these treatments. Here we found that most species performance metrics, but especially plant height, mainly were influenced by change in abiotic variables; if altered precipitation co-occurs with hay harvest, it negatively impacts plant performance.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We found that responses were species-specific as hypothesized. Our previous study 43 on species-specific responses to precipitation and clipping showed a small number of significant interactive effects between these treatments. Here we found that most species performance metrics, but especially plant height, mainly were influenced by change in abiotic variables; if altered precipitation co-occurs with hay harvest, it negatively impacts plant performance.…”
Section: Discussionmentioning
confidence: 85%
“…Permission to use this study site was obtained from KAEFS Steering Committee. The study site is dominated by C 4 and C 3 graminoids, and C 3 forbs 43 . Annual precipitation in 2017 was 992.12 mm (historical average in 1998–2016: 872.76 mm) and mean air temperature was 16.66 °C (historical average in 1998–2016: 16.15 °C) (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…70 cm, and a moderately penetrable root zone (Soil Survey Staff, Natural Resources Conservation Service, United States Department of Agriculture). The site is dominated by C 4 graminoids, C 3 annuals, and C 3 perennial forbs (Buthod & Hoagland, 2016; Castillioni et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The greater the important value, the greater the dominance. [20,21]. Set 9 plots for each degradation degree.…”
Section: Measurement Of Species Dominancementioning
confidence: 99%